2020
DOI: 10.21608/asnj.2020.79451
|View full text |Cite
|
Sign up to set email alerts
|

Self- esteem Among Male and Female Nursing Students Enrolled in Maternity Curriculum- Assiut University

Abstract: Background: The complex nature of nursing and midwifery as professions, and the challenges for students to achieve competencies to meet their profession's clinical and academic requirements all of this factors may have a negative effect on students' self-esteem. Aim: The study aims to assess the level of self-esteem among male and female nursing students enrolled in maternity curriculum, at Assiut University. Methods: Purposive sample of 475; (172 male and 303 female), third year nursing students, Faculty of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Additionally, the findings showed that female students had higher self-esteem than male students. These findings contrast with research conducted on Egyptian nursing students, which found that both male and female nursing students had moderate levels of self-esteem [ 43 ]. One explanation for that result is the presence of other factors that affect self-esteem, such as perceived prejudice, exposure to professional stress, and professional identity [ 44 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Additionally, the findings showed that female students had higher self-esteem than male students. These findings contrast with research conducted on Egyptian nursing students, which found that both male and female nursing students had moderate levels of self-esteem [ 43 ]. One explanation for that result is the presence of other factors that affect self-esteem, such as perceived prejudice, exposure to professional stress, and professional identity [ 44 ].…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, low self-esteem have been found as major problem in nursing professional. Therapeutic relationships with patients can only be developed by nursing students who have high levels of selfesteem (Fawzy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%